Executive functioning as mediator of the association between traumatic brain injury and prison bullying. (23rd February 2023) - Trajtenberg, Nicolás; Sánchez de Ribera, Olga; Cook, Steven; Ireland, Jane. L.
ABSTRACT: Objective: This study examined whether executive functioning (EF) mediated the relationship between childhood traumatic brain injury (TBI) and engaging in bullying in prison (BP) Participants: A sample of male adults in custody in Uruguay (N = 236), drawn from five prisons. Methods: Inmates filled out self-report questionnaires examining TBI ( Head Injury Questionnaire ), EF ( Behavior Rating Inventory of Executive Function Adult, BRIEF-A ) and bullying in prison ( Direct and Indirect Prisoner Behavior Checklist – revised, SCALED, DIPC-SCALED-r ). Results: Findings showed that TBI was associated with prison bullying after controlling for age, level of education, socioeconomic status, and civil status. The mediation analysis indicated that the relationship between TBI and bullying was fully mediated via executive impairment, especially through the behavioral regulation component (mainly inhibition and emotional control). Conclusion: These findings suggested that compensating for EF difficulties in adult inmates with brain injuries might help to decrease the bullying in prison.